Information Gaps in Aquatic Food System: Identifying India’s data gap - Dam Lam, Rodolfo; Shenoy, Neetha; Panemangalore, Arun; Rossignoli, Cristiano (WorldFish, 2023)
This study seeks to develop a pathway to identify and prioritize the main data gaps faced by key actors to develop a sustainable aquatic food systems that is both sensitive to vulnerable group needs and actionable by policymakers.